Macrophage activation by a vanadyl–aspirin complex is dependent on L-type calcium channel and the generation of nitric oxide - Molinuevo, María Silvina (2005)
Bone homeostasis is the result of a tight balance between bone resorption and bone formation where macrophage activation is believed to contribute to bone resorption.We have previously shown that a vanadyl(IV)–aspirin complex (VOAspi) regulates cell proliferation and differentiation of osteoblasts in culture. In this study, we assessed VOAspi and VO effects and their possible mechanism of action on a mouse macrophage cell line RAW 264.7. Both vanadium compounds inhibited cell proliferation in a dose-dependent manner. Nifedipine completely reversed the VOAspi-induced macrophage cytotoxicity, while it could not block the effect of VO. VOAspi also stimulated nitric oxide (NO) production, the oxidation of dihydrorhodamine 123 (DHR-123) and enhanced the expression of both constitutive and inducible isoforms of nitric oxide syntases (NOS). All these effects were abolished by nifedipine. Althogether our finding give evidence that VOAspi-induced macrophage cytotoxicity is dependent on L-type calcium channel and the generation of NO though the induction of eNOS and iNOS. Contrary, the parent compound VO exerted a cytotoxic effect by mechanisms independent of a calcium entry and the NO/NOS activation.